Anti-wear and friction-reducing lubricating oil additive and modified lubricating oil using the additive

Spherical h-BN nanoparticles were prepared by laser irradiation, and their dispersion was improved through magnetic stirring and ultrasonic dispersion, which solved the problem of poor dispersion of h-BN in mineral base oil, and realized the PAO6 base oil. Good dispersion and significant anti-wear and friction-reducing properties.

CN116496825BActive Publication Date: 2025-02-07JINAN YINHE ROAD & BRIDGE TEST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310447453.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-24
Publication Date
2025-02-07
Estimated Expiration
2043-04-24

AI Technical Summary

Technical Problem

In the prior art, the dispersion of h-BN in mineral base oils is poor, which limits its use. The method of preparing spherical h-BN particles is complex and contaminated, making it difficult to control spherical degree.

Method used

The nanosheets of hexagonal boron nitride are converted into spherical nanoparticles by laser irradiation, as lubricating oil additives, and their dispersion is improved through magnetic stirring and ultrasonic dispersion.

Benefits of technology

The good dispersion stability of h-BN nanospheres in PAO6 base oil is achieved, and the friction coefficient and the diameter of wear scars are significantly reduced, and the anti-wear and friction reduction performance of lubricating oil is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116496825B_ABST
    Figure CN116496825B_ABST
Patent Text Reader

Abstract

An anti-wear and friction-reducing lubricant additive and a modified lubricant using the additive. The lubricant additive is prepared from hexagonal boron nitride. Spherical hexagonal boron nitride nanoparticles are obtained by subjecting hexagonal boron nitride nanosheets to liquid-phase laser irradiation as a lubricant additive. The present application adopts a simple green laser irradiation method to prepare spherical hexagonal boron nitride nanoparticles. As a lubricant additive, the spherical hexagonal boron nitride nanoparticles have good dispersion stability in PAO6 base oil and exhibit excellent tribological properties. The one-step laser irradiation method of the present application provides a new way to prepare spherical hexagonal boron nitride nanoparticle lubricant additives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an anti-wear and friction-reducing lubricating oil additive and a modified lubricating oil using the additive. Background Art

[0002] Friction is a common phenomenon in nature, which usually leads to a large amount of energy waste in the processing process, shortens the machine life, and even causes potential safety hazards. Lubricating oil is the most effective strategy to reduce wear and improve machine efficiency. Lubricating oil is composed of base oil and additives. Therefore, developing new lubricating oil additives and continuously improving the anti-wear and friction reduction properties of additives are effective ways to improve the quality of lubricating oil.

[0003] Two-dimensional layered materials exhibit excellent tribological properties due to their special physicochemical properties. Among them, h-BN is a layered material with a graphite-like structure. Due to its good mechanical properties, lubricity and antioxidant properties, it is expected to become one of the first choices for green lubricant additives after reasonable development. In the past few decades, a large number of studies on h-BN as a lubricant additive have been reported. Some researchers have found that lipophilic BN nanosheets as friction additives in mineral oil can reduce the coefficient of friction (COF) by 20.2%. More importantly, the track of wear scars has become significantly shallower. Others have studied the tribological properties of BN as a PAO4 base oil additive. They found that after adding h-BN layered nanomaterials to the lubricant, the wear load of the lubricant was increased by 27% compared with the base oil. Other researchers have reported the successful exfoliation of BN nanosheets by combining hydrothermal treatment at 180°C and ultrasonic treatment. The exfoliated h-BN nanosheets have good friction reduction and anti-wear properties. However, the poor dispersibility of h-BN in mineral base oils limits its use, and the preparation of lipophilic h-BN remains a long-term challenge.

[0004] According to the anti-wear and friction reduction mechanism, due to the rolling action of the spherical particle molecular bearing and the rapid formation of the friction lubrication film effect between the friction pairs, the spherical particles have better lubrication properties. At present, the lubrication properties of many spherical particles have been studied, such as iron oxide, carbon balls, titanium dioxide, and tungsten disulfide. h-BN has a strong (002) plane directional growth tendency, is easy to form irregular flaky nanoparticles, and is difficult to prepare into a spherical shape. The currently reported preparation methods of h-BN spherical particles usually require a high temperature of more than 1800°C, the addition of urea, boric acid, ammonia and other chemicals, the preparation process is complicated and there is a certain amount of pollution, and the control of sphericity is still not ideal. Summary of the invention

[0005] In order to solve the above problems, the present application discloses an anti-wear and friction-reducing lubricant additive. The lubricant additive is prepared from hexagonal boron nitride. Spherical nanoparticles are obtained by laser irradiation of hexagonal boron nitride nanosheets as the lubricant additive.

[0006] Preferably, the nanosheets are processed as follows:

[0007] The hexagonal boron nitride nanosheets are placed in deionized water, and magnetic stirring and ultrasonic dispersion are performed to obtain a nanosheet dispersion liquid.

[0008] Preferably, the laser treatment is carried out in the following manner: irradiating a laser beam into the dispersion, the energy flux of the laser beam being 460-580 mJ pulse -1 cm -2 .

[0009] Preferably, the laser irradiation time is not less than 30 minutes.

[0010] Preferably, a KrF excimer laser with a laser beam wavelength of 248 nm is used as the laser irradiation source;

[0011] The laser beam is concentrated by a convex lens with a focal length of 150 mm and finally irradiated into the dispersion liquid to form a 0.7 cm 2 spot of light.

[0012] Preferably, the magnetic stirring and ultrasonic dispersion are performed alternately for no less than 3 times, and the time of each magnetic stirring is no less than 20 minutes and the time of each ultrasonic dispersion is no less than 20 minutes.

[0013] Preferably, the nanosheet dispersion treated by laser irradiation is filtered and dried to obtain a lubricating oil additive.

[0014] On the other hand, a modified lubricating oil is also disclosed, wherein the amount of the lubricating oil additive added to the lubricating oil is 0.05-0.2 wt %.

[0015] Preferably, the lubricating oil additive is added to the lubricating oil in an amount of 0.1 wt %.

[0016] Preferably, the average friction coefficient (COF) of the lubricating oil is reduced by 26.1%, and the wear spot diameter (WSD) of the friction pair is reduced by 23.2%.

[0017] The present application can bring the following beneficial effects: The present application adopts a simple green laser irradiation method to prepare spherical hexagonal boron nitride nanoparticles (Lh-BN). As a lubricating additive, the Lh-BN nanospheres have good dispersion stability in PAO6 base oil and exhibit excellent tribological properties. When the concentration of Lh-BN particles is 0.1wt%, COF and WSD are reduced by 26.1% and 23.2%, respectively, and the surface roughness and wear volume are reduced by 29.2% and 23.8%, respectively. The anti-wear and friction reduction mechanism mainly comes from two aspects. First, the effect of the Lh-BN spherical nanoparticle ball bearing leads to a low friction coefficient. In addition, as the friction process proceeds, some Lh-BN spherical nanoparticles are gradually peeled off to form a layered structure. The layered Lh-BN adheres to the wear surface to form a friction film, repairs the wear surface, and reduces wear. Therefore, the Lh-BN spherical nanoparticles have excellent anti-wear and friction reduction properties. The one-step laser irradiation method of the present application provides a new approach for preparing spherical Lh-BN lubricating oil additives. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0019] Figure 1 Schematic diagram of the growth process of Lh-BN spheres prepared in water by one-step laser irradiation.

[0020] Figure 2 (a) TEM image of pristine h-BN nanosheets, (b) Lh-BN nanospheres grown by laser irradiation, and (c) HTEM image of Lh-BN nanospheres.

[0021] Figure 3 (a) XRD spectra of pristine h-BN nanosheets and Lh-BN nanospheres, (b) Raman spectra of h-BN grown under different laser energy fluxes. XPS spectra of (c) N 1s core level and (d) B 1s core level of pristine h-BN nanosheets and Lh-BN nanospheres.

[0022] Figure 4 (a) Dispersion stability and (b) optical absorbance of pristine h-BN nanosheets and Lh-BN spherical nanoparticles in PAO6 base oil.

[0023] Figure 5COF curves of PAO6 base oil with different additives (a / c): (a) pristine h-BN nanosheets at different concentrations and (c) Lh-BN spherical nanoparticles at different concentrations. (b / d) The corresponding average COF and COF reduction compared to pure PAO6 base oil: (b) pristine h-BN nanosheets and (d) Lh-BN spherical nanoparticles.

[0024] Figure 6 WSD of (a) h-BN nanoflakes at different concentrations and (b) Lh-BN spherical nanoparticles at different concentrations with different additives in PAO6 base oil and the corresponding WSD reduction compared with PAO6 base oil.

[0025] Figure 7 White light interferometer images of the wear surface lubricated with PAO6 base oil: (a) plane 3D image, (b) stereo 3D image, (c) local magnified 3D image. White light interferometer images of the wear surface lubricated with PAO6 base oil containing 0.1wt% Lh-BN spherical nanoparticles: (d) plane 3D image, (e) stereo 3D image and (f) local magnified 3D image.

[0026] Figure 8 Optical images of the lubricated worn surfaces of (a) pure PAO6 base oil and (b) PAO6 base oil doped with 0.1 wt% Lh-BN, (c) Figure 8 (b) Enlarged image of the white box, (d) Raman intensity mapping image of h-BN.

[0027] Fig. 9 (a) SEM images of the wear surface of pure PAO6 base oil and (b) 0.1wt% Lh-BN lubricated wear surface, (c) N-dimensional mapping image of the friction pair surface lubricated with 0.1wt% Lh-BN, (d) Fig. 9 (b) EDS spectrum of midpoint 1, (e) Fig. 9 (b) N-element mapping image of the white box area.

[0028] Fig.10 Lubrication mechanism of Lh-BN additive. (a) Schematic diagram of four-ball friction, (b) nanosphere rolling friction, (c) interlayer slip of layered structure, (d) h-BN molecular structure. DETAILED DESCRIPTION

[0029] In order to clearly illustrate the technical features of this solution, this application is elaborated in detail below through specific implementation methods.

[0030] 1. Preparation of hexagonal boron nitride (h-BN) spherical nanoparticles

[0031] h-BN spherical nanoparticles were prepared by liquid phase laser irradiation. The raw material is hexagonal boron nitride. Unprocessed h-BN nanosheets (purity of 99.9%, Macklin) are irregular flakes. 50 mg of h-BN was added to a glass beaker containing 30 mL of deionized water, magnetically stirred for 20 minutes, ultrasonically dispersed for 20 minutes, and reciprocated three times, that is, magnetic stirring and ultrasonication were performed for a total of 3 times, the cumulative time was 60 minutes of magnetic stirring, and 60 minutes of ultrasonic dispersion, to obtain a uniformly dispersed h-BN solution. A KrF excimer laser (10 Hz, 25 ns, Coherent, CompexPro 205) with a wavelength of 248 nm was used as the laser irradiation source. The laser beam was concentrated by a convex lens with a focal length of 150 mm, and finally irradiated into the solution to form a spot of about 0.7 square centimeters. The energy fluxes were 460, 500, 540, and 580 mJ pulse, respectively. -1 cm -2 At the same time, the h-BN solution was magnetically stirred to ensure the uniformity of laser irradiation. The laser irradiation time was 30 minutes. After laser irradiation, the powder sample was dried for further characterization.

[0032] 2. Material Characterization

[0033] The x-ray diffractometer (XRD, D8-Advance, Bruker) used Cu-Kα line as the excitation source to obtain the x-ray diffraction pattern of the material under the conditions of 40kV and 40mA. The Raman scattering spectrum of the material was recorded using a Raman spectrometer (LabRAM HR Evolution, HORIBA) equipped with a 532nm laser. The binding energy of N and B in different samples was determined by x-ray photoelectron spectroscopy (XPS, Thermo Fisher, Al Kα x-ray source). The morphology of different samples was observed by transmission electron microscopy (TEM, JEM-2100Plus). The three-dimensional morphology and wear volume of the worn surface were observed using a white light interferometer (GTK-A, Bruker).

[0034] Tribological performance evaluation:

[0035] The friction and wear properties of the lubricant were tested using a four-ball friction and wear tester (MM-W1B, Jinan). When the equipment is working, the lubricant will fully penetrate into the four steel balls. During the friction process, the top steel ball rotates at a speed of ω under the action of the load f, and the three bottom steel balls are fixed together in the form of a bracket. The friction test was carried out at room temperature, with a rotation speed of 1000rpm, a load of 392N, and a test time of 30min. The steel ball has a hardness of 62HRC, a diameter of 12.7mm, and is made of GCr15 bearing steel. During the friction test, COF is automatically recorded. In order to ensure the accuracy of COF, the friction test was repeated three times for each concentration, and the COF was averaged.

[0036] Different energy fluxes (460, 500, 540, 580 mJ pulse -1 cm -2 ) Lh-BN spherical nanoparticles were added to PAO6 base oil at a concentration of 0.05wt%, and the friction test was carried out after thorough mixing. Energy flux was 540mJ pulse - 1 cm -2 The friction performance of the composite material is the best when the energy flux is 540mJpulse -1 cm -2 Taking h-BN spherical nanoparticles as an example, material characterization and tribological tests were carried out. 0.05wt%, 0.1wt%, 0.15wt% and 0.2wt% of h-BN nanosheets and Lh-BN spherical nanoparticles were added to PAO6 base oil respectively to obtain the optimal concentration.

[0037] After the friction test, the friction pair surface was cleaned with petroleum ether and then cleaned with alcohol three times. The three-dimensional profile of the worn surface was observed using a white light interferometer. The Raman scattering spectrum of the material on the worn surface was recorded. The surface morphology of the friction pair was observed using a scanning electron microscope (SEM, FEI Quanta 250FEG).

[0038] 3. Results and Discussion

[0039] 3.1 Preparation and characterization of Lh-BN spheres

[0040] like Figure 1 Shown is a schematic diagram of the growth process of Lh-BN spheres prepared in water by one-step laser irradiation.

[0041] Schematic diagram of the growth process of Lh-BN spherical nanoparticles under simple laser irradiation. Figure 1 As shown. During the laser irradiation process, high laser energy is instantly injected into the solution, producing a dissociation compression effect. And an extreme non-equilibrium state of ultra-high temperature and ultra-high pressure is induced at the interface between the laser beam and the material. The transformation of the particle morphology from flake to spherical is completed in one step. When the laser beam hits the original h-BN sheet for the first time, the laser spot immediately affects the material interface. Under such an impact, large pieces of h-BN explode into smaller fragments. Continuous pulsed laser irradiation causes heating and causes the surface of the h-BN particles to melt ( Figure 1 Process I). The original h-BN particles are rapidly cooled in a liquid environment and reshaped into nanospheres by a laser-induced photothermal process ( Figure 1 process II).

[0042] The morphology of the original h-BN nanosheets and Lh-BN spherical nanoparticles was characterized by transmission electron microscopy, as shown in Figure 2 As shown. The unprocessed h-BN nanosheets have a sheet-like structure and serious agglomeration phenomenon, such as Figure 2 (a). However, after simple laser irradiation, h-BN changes from a flake structure to a spherical structure, and the particles become looser. And the agglomeration phenomenon is suppressed. This is because under the action of laser irradiation, the absolute value of the Zeta potential on the particle surface increases, and the repulsive force between particles increases, thereby improving the dispersion of the particles. Compared with the original h-BN particles, the absolute value of the Zeta potential of laser-induced Lh-BN nanospheres increased by 50%. High-magnification transmission electron microscopy (HTEM) images show obvious lattice fringes with a lattice spacing of 0.33nm, which is the lattice spacing of the 002 plane of h-BN.

[0043] The phases of pristine h-BN nanosheets and Lh-BN spherical nanoparticles were analyzed by XRD. Figure 3 (a). All XRD diffraction peaks belong to the hexagonal phase of BN (JCPDS No.: 34-0421, P63 / mmc space group). The h-BN crystal morphology did not change before and after laser irradiation. The diffraction peaks of h-BN are (002), (100), (101), (004), (110) and (112). After laser irradiation, the intensity of the main reflection peak decreased, which may be caused by the change of particle morphology from flake to spherical. Figure 3 (b) Raman spectra of h-BN grown under different laser energy fluxes. 1366cm -1 The sharp Raman peak at comes from the high-frequency characteristic peak of h-BN. The high-frequency Raman characteristic peak shows a slight blue shift, which can be attributed to the residual strain in the spherical structure.

[0044] The XPS spectra N1s and B1s spectra of pristine h-BN nanosheets and Lh-BN spherical nanoparticles are shown in Figure 2. Figure 3 (c) and (d). It is worth noting that the binding energy of N1s and B1s shifted to a certain extent after laser irradiation. For the original h-BN nanosheets, the position of the N1s peak is 397.91ev, and the position of the B1s peak is 190.29ev. The N1s peak position of the laser-induced Lh-BN nanospheres is 397.43ev, and the B1s peak position is 189.85ev. The binding energy is reduced, and the results further confirm that after laser irradiation, the particles are transformed from flakes to spheres.

[0045] Good dispersion of nanoparticles in base oil is a prerequisite for lubrication applications. The raw materials h-BN nanosheets and Lh-BN nanospheres were used as additives and added to PAO6 base oil at a concentration of 0.1wt%. For the oil sample containing Lh-BN spherical nanoparticles, no obvious precipitation phenomenon was observed after 30 days, indicating that the nanoparticles can be stably dispersed in the base oil. In contrast, the oil sample containing h-BN nanosheets showed obvious precipitation after 3 days ( Figure 4 (a)). In order to further examine the dispersion stability, the absorbance curves of PAO6 base oil containing original h-BN nanosheets and Lh-BN nanospheres were measured by UV-visible spectrophotometer ( Figure 4 (b)). After adding the original h-BN nanosheets, the absorbance (λ = 430 nm) of the PAO6 base oil decreased rapidly over time. However, the absorbance of the PAO6 base oil containing Lh-BN spherical nanoparticles was very stable, which also confirmed that the Lh-BN spherical nanoparticles had good dispersion stability in the PAO6 base oil as an additive.

[0046] The tribological properties of Lh-BN spherical nanoparticles were evaluated by four-ball tribological test. The addition concentrations of h-BN nanosheets and Lh-BN spherical nanoparticles were 0.05wt%, 0.1wt%, 0.15wt% and 0.2wt%, respectively. Figure 5 (a) is the COF curve of h-BN nanosheets as PAO6 base oil additives at different concentrations. The COF of pure PAO6 base oil has certain fluctuations. However, with the addition of h-BN nanosheets, the COF decreases. For h-BN nanosheets, when the concentration is less than 0.15%, the COF decreases with the increase of h-BN nanosheets. When the concentration of h-BN nanosheets is 0.1wt%, the average COF decreases the most, reaching 16.2%. With the increase of h-BN nanosheet concentration, COF increases. The COF curve of the oil sample containing 0.1wt% Lh-BN spherical nanoparticles is much smoother than that of the oil sample containing 0.1wt% h-BN nanoflakes, as shown in Figure 2. Figure 5 (a) and (c). When the concentration of Lh-BN spherical nanoparticles added was 0.1wt%, the average decrease in COF was the largest, reaching 26.1% ( Figure 5 d), has a good friction reduction effect. This is because the h-BN nanosheets have poor dispersibility in the base oil, and the aggregated h-BN nanosheets easily scratch the surface of the friction pair, and the friction performance of the additive is not optimal. The Lh-BN spherical nanoparticles with good dispersion stability spread between the friction pairs to form a good lubricating film. In addition, the spherical h-BN nanoparticles have a good rolling friction effect, thereby reducing COF.

[0047] Lubricant additives should not only have good anti-wear properties, but also excellent anti-wear properties. After the friction test, the wear spot diameter (WSD) data on the lower fixed ball was studied ( Figure 6 ). After adding h-BN nanoflakes and Lh-BN spherical nanoparticles, the wear scar diameter decreases, indicating that the additives play an anti-wear role. However, when the concentration is greater than 0.1wt%, the anti-wear effect begins to weaken. This is because as the concentration of the additive increases, the excess additive forms agglomerates, resulting in severe wear. When the concentration of Lh-BN spherical nanoparticles is 0.1wt%, the WSD decreases the most, reaching 23.2%. However, the dispersion effect of h-BN nanosheets is not as good as that of Lh-BN spherical nanoparticles. When the concentration of h-BN nanosheets is 0.2wt%, the WSD increases compared to pure PAO6 base oil, which is the result of severe wear caused by agglomeration. The excellent anti-wear performance mainly comes from two aspects. One is that the ball bearing effect leads to a low friction coefficient, thereby reducing wear. On the other hand, after a long period of friction, the Lh-BN spherical nanoparticles will gradually peel off and transform into a layered structure during the friction and extrusion process. As the friction process proceeds, the layered structure will adhere to the surface of the friction pair, reduce the wear on the surface of the friction pair, and repair the friction pair.

[0048] After the friction experiment, the three-dimensional image of the wear on the friction pair surface is as follows Figure 7 When Lh-BN is not added, the friction pair surface is severely worn, and the grooves are deeper and wider ( Figure 7 a, b). Partially enlarged three-dimensional image ( Figure 7 c) shows that the wear surface fluctuates severely. After adding Lh-BN spherical nanoparticles, the wear phenomenon is alleviated and the fluctuation of the wear surface is greatly reduced, such as Figure 7 (df) is shown. The locally enlarged 3D image also shows that the wear surface is relatively uniform and smooth. The surface roughness Ra of the friction pair after the pure PAO6 base oil friction test is 3.012μm, and the surface roughness Ra of the friction pair after the Lh-BN lubrication friction test is 2.132μm. At the same time, after adding the Lh-BN additive, the wear volume is reduced from 0.0021mm 3 Reduced to 0.0016mm 3 , a decrease of 23.8%, indicating that the Lh-BN additive has a good anti-wear effect.

[0049] To study the lubrication mechanism, Raman spectroscopy was used to analyze the worn surface. Figure 8 As shown. The wear marks on the wear surface lubricated with pure PAO6 base oil are deep and wide ( Figure 8 (a)), which is consistent with the wear traces observed by white light interferometry. Raman analysis of the friction zone shows that the -1There is an obvious iron oxide peak at the friction pair, indicating that the friction pair surface is severely worn. For the sample containing Lh-BN, the worn surface is smooth ( Figure 8 (b)). Raman spectrum of the worn surface ( Figure 8 (b)) and Raman plane scanning mode ( Figure 8 (c, d)) both show obvious Lh-BN signals, indicating that the Lh-BN additive is uniformly deposited on the friction pair. Therefore, the Lh-BN additive can effectively form a friction film and play a good role in surface repair, thus showing a significant anti-wear effect.

[0050] Fig. 9 (a, b) are SEM images of the worn surface after friction test with pure PAO6 base oil and Lh-BN additive, respectively. As can be seen from the figure, the worn surface after lubrication with pure PAO6 base oil is uneven and the wear spot diameter is large. The worn surface after lubrication with PAO6 base oil containing Lh-BN additive is smooth and the wear spot diameter is small. The chemical composition of the worn surface was analyzed by energy dispersive spectrometer (EDS), such as Fig. 9 (ce) shows. The N element mapping image and EDS spectrum show that the Lh-BN additive wear surface contains N elements, proving that the Lh-BN additive is successfully deposited on the friction pair surface. After the friction test, the distribution of N elements is spherical, which is consistent with the appearance of the wear point, indicating that h-BN is successfully deposited on the friction pair surface to form a friction film, which plays a good repair role.

[0051] The lubrication mechanism of Lh-BN as a lubricant additive is as follows Fig.10 As shown. Lh-BN nanospheres can be well dispersed in the base oil as additives. During the friction process, spherical nanoparticles can convert sliding friction into rolling friction, thereby reducing COF, such as Fig.10 (b) In addition, some Lh-BN spherical additives are peeled into layers during the friction pair extrusion process. The lower shear force between the layered structures can also reduce COF. As the friction process proceeds, the layered structure will be adsorbed on the surface of the friction pair to form a friction film, repairing the friction pair, thereby reducing surface wear and playing an anti-wear role ( Fig.10 (c)). In summary, under the combined effect of the above two mechanisms, the Lh-BN spherical nanoparticles as additives exhibit excellent anti-wear and anti-friction effects.

[0052] In summary, Lh-BN spherical nanoparticles were prepared by a simple green laser irradiation method. As a lubricating additive, Lh-BN nanospheres have good dispersion stability in PAO6 base oil and exhibit excellent tribological properties. When the concentration of Lh-BN particles is 0.1wt%, COF and WSD are reduced by 26.1% and 23.2%, respectively, and surface roughness and wear volume are reduced by 29.2% and 23.8%, respectively. The anti-wear and friction reduction mechanism mainly comes from two aspects. First, the effect of ball bearings leads to a low friction coefficient. In addition, as the friction process proceeds, part of the Lh-BN spherical nanoparticles are gradually peeled off to form a layered structure. The layered h-BN adheres to the wear surface to form a friction film, repairs the wear surface, and reduces wear. Therefore, Lh-BN spherical nanoparticles have excellent anti-wear and friction reduction properties. This simple one-step laser irradiation method provides a new way to prepare spherical Lh-BN lubricant additives.

[0053] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. An anti-wear and friction-reducing lubricating oil additive, characterized in that: The lubricating oil additive is prepared from hexagonal boron nitride, and the spherical nanoparticles obtained by laser irradiation of hexagonal boron nitride nanosheets are used as the lubricating oil additive; The nanosheets are processed as follows: The hexagonal boron nitride nanosheets are placed in deionized water, and subjected to magnetic stirring and ultrasonic dispersion to obtain a nanosheet dispersion liquid; The laser irradiation is carried out in the following manner: irradiating the dispersion with a laser beam having an energy flux of 460-580 mJ pulse. -1 cm -2 , laser irradiation time is not less than 30min; A KrF excimer laser with a laser beam wavelength of 248 nm was used as the laser irradiation source; The laser beam is concentrated by a convex lens with a focal length of 150 mm and finally irradiated into the dispersion liquid to form a 0.7 cm 2 spot of light.

2. The anti-wear and friction-reducing lubricating oil additive according to claim 1, characterized in that: The magnetic stirring and ultrasonic dispersion are performed alternately for no less than 3 times, and the duration of each magnetic stirring is no less than 20 minutes and the duration of each ultrasonic dispersion is no less than 20 minutes.

3. The anti-wear and friction-reducing lubricating oil additive according to claim 1, characterized in that: The nanosheet dispersion treated by laser irradiation is filtered and dried to obtain a lubricating oil additive.

4. A modified lubricating oil using the lubricating oil additive according to any one of claims 1 to 3, characterized in that: The lubricating oil additive is added in an amount of 0.05-0.2 wt % in the lubricating oil.

5. A modified lubricating oil according to claim 4, characterized in that: The lubricating oil additive is added in an amount of 0.1 wt % in the lubricating oil.

6. A modified lubricating oil according to claim 5, characterized in that: The average friction coefficient of PAO6 base oil after adding lubricant additives was reduced by 26.1%, and the wear spot diameter of the friction pair was reduced by 23.2%.

Citation Information

Patent Citations

  • A laser liquid phase annealing method for preparing oxide microspheres with anti-wear effect and its application

    CN102267716A

  • Quick in-situ preparation method of noctiluca-shaped graphene wrapped silicon carbide microsphere

    CN107686761A